Justo Sierra O'Reilly and John L. Stephens: Translation, History, and Transnational Romanticisms in the Americas. Issue 1 (2nd January 2019) - West, Ty
Abstract : In this article, I explore the crossroads that unite two important nineteenth-century travel writers from the Americas: John L. Stephens who traveled south from the U.S. to the Yucatán peninsula, and Justo Sierra O'Reilly who traveled north from the Yucatán to Washington D.C. By focusing on two writers from the Americas, my goal is to examine how Romantic aesthetics and ideologies took on new shapes through cultural exchange within the region. More specifically, I study how these two travel writers articulated and came to terms with what Stephen Bann has identified as two fundamental aspects of the Romantic period. The first is the 'remarkable enhancement of the consciousness of history' (Bann1995, 4) evident in the importance of popular literary genres like the historical novel. The second is a new accessibility to texts and information that incorporated large groups of readers and made historical information more available. While Stephens demonstrates an at times romantic fascination with indigenous history constructed through the analysis of the ruins he visits, Sierra O'Reilly's translation, at every turn, critically engages Stephens's historical conclusions, revealing interlocking and contested notions of history in the Americas.